Examining the Impact of Human Resource Information System on Organizational Performance: Mediating Effect of Employees Performance - Arfan Saeed; Shanayyara Mahmood; Muhammad Shafiq Anwar (`, 2026)
Human resource is the key that drive the organization towards the success but for this, personnel should be skilled, properly deployed and effectively controlled. SIS and HRMIS were introduced by the GOP for the said purpose. This study examined the impact of HRIS on the organizational performance with mediating effect of adaptive performance in the school education department. Stratified sampling technique was used to collect the data. Total 333 proper questionnaire were received for data analysis. Initially factorization was run on HRIS and in total 4 factors were derived. Smart PLS was used for further data analysis. It was found that operational efficiency & decision support has positive but insignificant impact on organizational performance. User engagement & satisfaction also have insignificant impact on organizational performance. Process optimization & cost reduction has positive and significant impact on organizational performance. Time & cost efficiency also has positive and significant impact on the organizational performance. It was observed a significant relationship between adaptive performance and organizational performance. Indirect effect of adaptive performance was found statistically insignificant between operational efficiency & decision support on organizational performance. Indirect effect of adaptive performance was also found statistically insignificant between User engagement & satisfaction on organizational performance. Adaptive performance mediates the relationship of Process optimization & cost reduction and organizational performance. Time & cost efficiency mediates the relationship of process optimization & cost reduction and organizational performance. Keywords. HRIS, Adaptive Performance and Organizational Performance